Emerging shift and merger: Acoustic analysis in received pronunciation vowel production by Mandar EFL learners - Siti Radibah Imatufariq; Achmad Rio Dessiar (Universitas Muhammadiyah Purwokerto, 2026)
This study aims to investigate differences in the production of received pronunciation vowels /ɑː/ and /æ/ between Mandar EFL learners and native speakers, as well as the distribution of vowel patterns across participants' academic levels, using a mixed qualitative and quantitative approach. There are 5 words in this current research that contain the initial vowels/ɑː/ and /æ/: 'afternoon', 'answer', 'apple', 'animal', and 'actor'. To examine the vowel difference, this research used audio recordings from 10 participants: 5 from the 5th semester and 5 from the 1st semester. The audio recordings were analyzed with PRAAT to measure openness using F1 and tongue position using F2. The formant data were then normalized using the Lobanov normalization to avoid confounding by gender, age, and physiological variables. The analysis was conducted to figure out the distinction pattern of vowel articulation by Mandar and native speakers, and the possibility of vowel shift and merger. The results indicate a significant difference in vowel production between Mandar and native speakers, as confirmed by the t-test. The articulatory distinction between a Mandar native speaker and a native speaker is reflected in the articulation of the vowel /æ/ that shifts in all contexts. Meanwhile, the vowel /ɑː/was articulated differently across contexts by Mandar speakers. The findings showed that Mandar speakers exhibit vowel shifting and merger, which are caused by the assimilation of L2 sounds to L1 and by the quantity-quality of L2 input. Moreover, the results appear to support the SLM-r hypothesis in phonetic formation in L2 acquisition.